The Legalization of Medical Marijuana: A Human Rights Law Perspective - Aditya, Zaka Firma; Al Fatih, Sholahuddin (Human Rights in the Global South (HRGS), 2022)
The discourse on legalizing marijuana for medical purposes in Indonesia peaked when legislators discussed the draft law on the narcotics law amendment. Efforts to legalize marijuana for medical purposes have also been pursued by testing the narcotics law. However, through decision number 106/PUU-XVII/2020, the Constitutional Court prohibited medical marijuana as a medical treatment. From the Human Rights perspective, everyone has the right to life and health. Therefore, in society's logic, the prohibition of using marijuana for medical treatment is the same as forbidding sick people to stay alive. It means that the state has failed to guarantee its citizens' lives. But on the other hand, several countries legalized medical marijuana, such as Thailand, Turkey, Lebanon, Netherlands, and Spain. So, why is Indonesia still banning the use of medical marijuana? This research tries to find the legal reasoning of Indonesia's government in the medical marijuana case. These problems were then analyzed using the prescriptive method with a comparative approach to finding new concepts related to legalizing medical marijuana in Indonesia. This study indicates that medical marijuana may be legal in the future of Indonesia's regime. It demonstrates by Indonesian Ulema Council and the Ministry of Health's political wills. The research recommendations are to provide proper education about medical marijuana and the prospect of legalization in the future.